2020
DOI: 10.12765/cpos-2020-14
|View full text |Cite
|
Sign up to set email alerts
|

Lone Mothers' Employment Trajectories: A Longitudinal Mixed-method Study

Abstract: Using a mixed-method design, this study explores the heterogeneity in employment trajectories before and after the transition to lone parenthood in Switzerland. First, we perform sequence and cluster analysis on data from the Swiss Household panel to identify typical employment trajectories around the transition to lone parenthood, and then estimate their association with individual and household characteristics (N=462). Finally, we contrast these results with findings from a content analysis of narrative inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Specifically, individuals experiencing marital instability, those with unsupportive social networks [23], those without children, and most specifically women [4] are at risk of feeling socially lonely, underscoring the importance of social resources. In countries with strong societal norms, such as in Switzerland, gender is an important factor to consider, as the dissolution of marriage is more challenging for women than for men [24]. Women are encouraged to reduce their employment rates or stop any work activity after marriage or motherhood, leading to poorer financial and social resources.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, individuals experiencing marital instability, those with unsupportive social networks [23], those without children, and most specifically women [4] are at risk of feeling socially lonely, underscoring the importance of social resources. In countries with strong societal norms, such as in Switzerland, gender is an important factor to consider, as the dissolution of marriage is more challenging for women than for men [24]. Women are encouraged to reduce their employment rates or stop any work activity after marriage or motherhood, leading to poorer financial and social resources.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the GSOEP does not provide sufficient information on non-residential fathers' involvement. Prior research finds that the father's reliability regarding negotiated childcare arrangements and maintenance payments is a crucial precondition for lone mothers to accomplish their dual roles as main carers and main earners (Struffolino et al 2018). Hence, a certain bias may remain due to time-varying unobservable characteristics influencing both the likelihood of becoming a lone mother and of being poor (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Some mothers tried to adjust to such situations by increasing their own income from paid work, which had repercussions in other life domains. For example, when these mothers increased their working hours, they often struggled to find appropriate childcare (Struffolino et al 2020). The author concluded that even welfare institutions that are designed to protect lone parents against poverty and overburden fail to realise that lone mothers' choices are primarily guided by their 'ethic of care'.…”
Section: The Relationship Between Institutions and Familiesmentioning
confidence: 99%